2019
DOI: 10.1002/ecs2.2825
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Quality Assessment: a critique, a defense, and a primer

Abstract: Floristic Quality Assessment (FQA) measures have become extraordinarily influential ecological metrics in North America over the past 20 yr. Government agencies, conservation organizations, land managers, and researchers alike utilize this plant-based measure to evaluate habitat conservation value, ecological integrity, and naturalness. Its relative uniqueness, utility, and ease of use, among vegetation measures, portend the continued popularity of FQA going forward. FQA's use and influence far exceeds its stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…They caution that species with inherently larger growth forms or high population densities could unduly influence abundance-weighted measures. Conversely, other authors question whether such measures de-value species that are inherently rare in plant communities [ 71 ]. Some studies of abundance-weighted FQA measures have found little or no improvement over non-weighted measures [ 72 , 73 ] or improvement only in a small subset of habitats [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…They caution that species with inherently larger growth forms or high population densities could unduly influence abundance-weighted measures. Conversely, other authors question whether such measures de-value species that are inherently rare in plant communities [ 71 ]. Some studies of abundance-weighted FQA measures have found little or no improvement over non-weighted measures [ 72 , 73 ] or improvement only in a small subset of habitats [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient of conservation, an index for vascular plants that is similar to the lichen conservation index we present here, has a long history of use by botanists and land managers but has also been criticized at times (Spyreas 2019). Because values are assigned by experts, rather than based on field data, some researchers have suggested that they may be biased.…”
Section: Discussionmentioning
confidence: 99%
“…Land managers around the globe are tasked with conserving biodiversity, and must evaluate the conservation value of ecological communities to develop conservation plans. Managers frequently seek to identify the extent to which communities contain species with affinities for undisturbed, late-successional habitats, since these are often the most imperiled species in contemporary landscapes that have largely been altered by anthropogenic activities (Veldman et al 2015, Spyreas 2019. Identifying communities that contain late successional species can allow managers to evaluate the results of management practices and may facilitate the comparison of different areas or land parcels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations